"TEMUR TRAPS" THROUGH THE EYES OF WORLD HISTORIANS (International journal of artificial intelligence, 2026)
This article describes the biography of Amir Temur, his socio-political activity, his seizure of central power in Movarounnahir, the elimination of political fragmentation, the formation of a centralized state, the inclusion of 27 countries in his classification. It discusses who to trust in the administration of the state, the attitude and duties of the holders of the crown, the choice of ministers and commanders of the army, the structure of the army and the rules of warfare, the salaries of soldiers, the order of governing the country, the duties and duties of statesmen and commanders of the army, the way of rewarding the special services rendered by superiors, ministers and other officials before the crown and much more.